ANALISIS ANXIETY MAHASISWA DALAM PRAKTIK PERAKITAN KOMPUTER DI PERGURUAN TINGGI - Fadli, Radinal; Wahyudi, Dwi (Information Technology Education Department, 2025)
Anxiety is an emotional response to situations perceived as threatening, and in the context of practical learning, anxiety can affect students' readiness, concentration, and performance. This study aims to analyse students' anxiety levels during computer assembly practice in the Information Technology Education study program. The method used was descriptive quantitative, involving 80 students as respondents. The research instrument was a five-point Likert scale questionnaire to measure anxiety levels. The results showed that students' anxiety levels were in the moderate to high category, with anxiety about technical errors and assembly procedures as the highest indicators. This finding indicates that students feel stressed by the possibility of errors and uncertainty in following the assembly stages. The findings of this study indicate the need for a more supportive learning approach, such as technical assistance, simulations, and project-based learning, to reduce anxiety. The limitation of this study lies in the quantitative approach that has not explored psychological factors in depth. Therefore, further research is recommended using a qualitative or mixed approach to better understand the dynamics of student anxiety in technical practice.